(3EjVGM GdeTcd ef GdebQHs - (3GHf YUahQ , Ydj Hf eDef Hf eMeO GdMVQej GdGTHjdj, CHh GdMSf,J (B669 (3g` s
(3ChdgG (B:s
(3hHYO, aEfj deG SdcJ aj cJGHj GdeSei GdebqQH eSdc GdGNJUGQ s
(3BNQgG (B:s
(3hbO Qhi GdHjJ HKdGKI GdChLg, hCeG JLhjRge Pdc ajg YfO GdGVWQGQ aYdjg CcKQ GdVQGFQ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfjs
(3fSNI egedI GdfbW cKjQkGs
(3hHgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B27s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B546 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B44 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1805s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdfMhs